PENGARUH LATIHAN PERMAINAN TARGET TERHADAP KETEPATAN SHOOTING DALAM PERMAINAN FUTSAL RAJAWALI CLUB - Yosefa Zik Alendra; Imam Mahfud (Universitas Teknokrat Indonesia, 2022)
The purpose of this study was to develop a futsal game using a futsal target game training model that was adapted to the characteristics of children at the Rajawali Club. The research method used in this research is experimental research with a two group pretest posttest design research design. The subjects in this study were high school students who participated in the Rajawali futsal club, totaling 40 people who were divided into two groups. The stages in this research are carrying out a pretest to find out initial data from students using a test instrument (Arki Taupan Maulana) then giving treatment to the experimental group for 16 meetings using 8 target game training models and finally carrying out a posttest to find out the changes that occur after given treatment. The results of this study indicate that the futsal target game training model has a significant effect on the shooting ability of the experimental group (treatment), this can be seen from the pretest data that lies on average 32.95 and when the posttest averages 38.70. with an increase of5.75. which means that there is an effect of the futsal target game training model on the shooting ability of Rajawali Futsal Club players.